S-propargyl-cysteine promotes the stability of atherosclerotic plaque via maintaining vascular muscle contractile phenotype - Ping, Li; Zhi-Ming, Li; Bi-Shan, Zhang; Lei, Zhu; Bo, Yu; Yi-Chun, Zhu; Ming-Jie, Wang (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Plaque rupture in atherosclerosis contributes to various acute cardiovascular events. As a new sulfide-containing donor, S-propargyl-cysteine (SPRC) has been reported to play a beneficial role in cardioprotection, potentially through its anti-inflammatory, anti-oxidative and anti-atherogenic activities. Our previous study observed an increase in eNOS phosphorylation in endothelial cells. However, it remains unclear whether SPRC influences vascular smooth muscle cells (VSMCs) within the plaque and if this effect contributes to plaque stabilization. Methods: An atherosclerotic unstable plaque mouse model was established by subjecting ApoE−/− mice to tandem stenosis of the right carotid artery along with a Western diet. Daily SPRC administration was conducted for 13 weeks. Plaque morphology and stability were assessed using MRI scanning and histopathological staining. In our in vitro studies, we stimulated human artery vascular smooth muscle cells (HAVSMCs) with platelet-derived growth factor-BB (PDGF-BB), both with and without 100 μM SPRC treatment. Cell phenotype was assessed using both Western blot and Real-time PCR. Cell proliferation was assessed using the BrdU cell proliferation kit and immunofluorescence of Ki-67, while cell migration was measured using scratch wound healing and transwell assay. MiR-143-3p overexpression and knockdown experiments were used to investigate whether it mediates the effect of SPRC on VSMC phenotype. Results and Discussion: SPRC treatment reduced plasma lipid levels, increased collagen content and decreased cell apoptosis in atherosclerotic plaques, indicating improved plaque stability. Both in vivo and in vitro studies elucidated the role of SPRC in preserving the contractile phenotype of VSMCs through up-regulation of miR-143-3p expression. Furthermore, SPRC suppressed the pro-proliferation and pro-migration effects of PDGF-BB on HAVSMCs. Overall, these findings suggest that the inhibitory effect of SPRC on phenotype switch from contractile to synthetic VSMCs may contribute to its beneficial role in enhancing plaque stability.